The role of events and music festivals in urban tourism: case study - Liberato, Dália (2019)
The city of Oporto assumes a decisive role in the North region of Portugal, as a tourism destination. In addition to the recognized material and intangible heritage, the city has been developing strategies to create partnerships with regional and national stakeholders in order to program events of different typologies, throughout the year, with benefits for the city and the region. The music festivals are one of the activities programmed with the greatest expression in the city, nowadays. The present research, integrated in a broader project, aims to highlight the importance of the programming of events. In view of this purpose, this article will discuss the need to adapt music festivals to the target audience, in order to adjust the offer with positive results at the level of behavioural attitudes of tourists, regarding the intention to repeat and recommend the event (and destination).